Формування "малоросійської позиції" газети "Киевлянин" у 1917 р.: причинки до краху "малоросійського проекту" - Гаухман, М. (Краєзнавство, 2017)
У статті розглянуті публікації газети «Киевлянин» квітня–червня 1917 р., присвячені «малоросійському руху», критиці українського руху та міжконфесійним відносинам на західноукраїнських землях. На підставі аналізу публікацій сформульований чинник слабкості «малоросійського проекту» – відсутності вимог національної та соціальної емансипації. The article deals with the journalism of newspaper «Kievlyanin» in first part of 1917 toward «Little Russian
movement», Ukrainian question and confessional interrelations in the West Ukraine. The «Kievlyanin» was
the influential agent of «Little Russian Project», which evidenced in the nation-making process in early XX century.
The «Little Russian Project» was the activity of Russian nationalists from ethnic Ukrainians, who suggests
Ukrainians as «Little Russians» – the branch of «Great Russian people».
The «Kievlyanin» in April–June 1917 – from first regular anti-Ukrainian publications to the First Universal
of the Ukrainian Central Rada – published some articles about activity of «Little Russian» (or «South Russian»)
organizations and a lot of articles toward Ukrainian question, which were against Ukrainian national movement,
Ukrainian Central Rada, Ukrainization of education and army. Besides the «Kievlyanin» published open
letters in defense of confession policy in Galicia under Russian occupation in 1914–1915 and about Austrian
repressions against «Russophiles».
The analyses of these materials demonstrate that the redaction of «Kievlyanin» continued prerevolution
interpretation of Ukrainian national movement as anti-Russian power. The novelty of 1917 was recognition of
Ukrainian movement, but as narrow party, not national movement. In general, the newspaper advocated positions
of status quo in national and social questions. In publications by «Kievlyanin» Ukrainians looked like as
«Little Russians», which weren’t required national and social emancipations. That’s why the «positive» publication
about «Little Russian» (or «South Russian») organizations took less spaces that «informative» and «negative
» materials about Ukrainian movement. Besides «Little Russian» organizations arose later and were less
influential than similar Ukrainian organizations. In our view, the ideological stagnation of «Kievlyanin»’s
position in national and social questions was the factor of crush of the «Little Russian Project». В статье рассмотрены публикации газеты «Киевлянин» апреля–июня 1917 г., посвящённые «малороссийскому движению», критике украинского движения и межконфессиональным отношениям на
западноукраинских землях. На основании анализа публикаций сформулирован фактор слабости «малороссийского проэкта» – отсутствии требований национальной и социальной эмансипации.